Bioactive Potential of Hexane Extract from Plumbago europaea Roots: Chemical Composition and Antimicrobial, Anti-inflammatory, and Hemolytic Activities - Soltani, Yassamine Ikram; Keniche, Assia; Dib, Mohammed El Amine; Arrar, Zoheir; Muselli, Alain (Anti-Infective Agents, 2026)
IntroductionPlumbago europaea, commonly known as European Dentellary, has been traditionally used across various cultures to treat numerous ailments. This study aims to explore the therapeutic potential of this plant, focusing on its chemical composition and biomedical applications.ObjeictiveThe objective of this study was to characterize the chemical composition of the hexane extract from the roots of Plumbago europaea and evaluate its antimicrobial, anti-inflammatory, and hemolytic activities.MethodsThe chemical profile of the hexane root extract of Plumbago europaea was analyzed using Gas Chromatography-Flame Ionization Detection (GC-FID) and Gas Chromatography-Mass Spectrometry (GC-MS). Antimicrobial activity was assessed using the disc diffusion and micro-well dilution methods. The anti-inflammatory effects were evaluated through the egg albumin denaturation assay. Hemolytic activity was measured by assessing erythrocyte lysis in human blood samples.Results and DiscussionChemical analysis of the hexane extract identified nine compounds, with plumbagin (58.4%) being the most abundant, followed by nonanal (16.6%). The antimicrobial assay demonstrated significant growth inhibition against several bacterial strains, including Micrococcus luteus, Bacillus cereus, Staphylococcus aureus, and the yeast Candida albicans. The anti-inflammatory tests indicated that the hexane extract exhibited potent activity, with an IC50 of 12.3 μg/mL, surpassing diclofenac (IC50: 35.2 μg/mL). Hemolysis tests revealed minimal erythrocyte damage, with a hemolytic rate of only 12.86%, even at higher concentrations.ConclusionThe hexane extract from Plumbago europaea roots demonstrates promising antimicrobial and anti-inflammatory activities with minimal toxicity to human erythrocytes. However, further studies are needed to validate these findings and explore the plant's potential for pharmaceutical development.
Keywords: albumin denaturation